Hacia el origen de los vascos. Secuencias de DNA mitocondrial antiguo del País Vasco. - García Bour, Jaime; Turbón, Daniel; Valdés, Luis; Fernández, Eva; Arenal, Isabel; Pérez Pérez, Alejandro (Complutum, 2000)
Sin resumen